Multiple periannular defects after an inadequate mitral valve repair procedure and unsuccessful redo valve surgery with pericardial patches in an elderly patient - Toprak, Cüneyt; Avcı, Anıl; Yanartas, Mehmed; Mustafa Tabakcı, Mehmet; Acar, Emrah; Ozkan, Mehmet (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
The fastest growing demographic group in Europe and America is the elderly, and significant mitral regurgitation is very prevalent in this population. At present, with mitral valve surgery in elderly individuals gaining greater acceptance worldwide, the question whether to repair or replace the valve remains controversial. Recent studies have demonstrated the safety, feasibility, and durability of repair over replacement in elderly patients. Herein, we report the case of an elderly patient who underwent surgical re-interventions on the mitral valve following an unsuccessful mitral valve repair procedure.